MANAGEMENT OF PENETRATING INJURY TO THORACIC INLET AND LOWER NECK WITH RETAINED FOREIGN BODY USING VIDEO ASSISTED THORACOSCOPIC SURGERY - Samad, Muhammad Adeel; Khan, Hamza Abdur Rahim; Urooj, Faiza; Hyder, Usman Ali; Khan, Fazal Wahab; Fatimi, Saulat Hasnain; Khan, Jamal Kabeer (Journal of Ayub Medical College Abbottabad, 2017)
Penetrating neck and chest injuries are a common form of occupational injuries. We hereby report a unique case in which a metallic rod had penetrated the left chest and neck of a plastic factory worker. The patient was vitally stable when he presented to Emergency Room. Chest X-ray was performed and the patient was rushed to the operating room. VATS (video assisted thoracoscopic surgery) and neck dissection was done for retrieval of the metallic rod. On table, endoscopy was also done to rule out injury to oesophagus. No injury to vital structures was found and the subsequent recovery was uneventful. Keywords: VATS; penetrating injury; thoracic inlet; lower neck